Community Education and Training on Basic Life Support for Teachers and Students of SMP Inspirasi - Firmansyah, Andan; Hamdani, Dadi; Setiawan, Henri; Suhanda, Suhanda; Safariani, Nur; Rohimah, Sri Nurul; Sari, Wiar (Yayasan Inspirasi El Burhani, 2025)
Introduction: Cardiac arrest is a medical emergency that requires immediate intervention by medical personnel or trained individuals. High mortality rates are often due to the lack of skills among bystanders in providing timely assistance. Objective: This community service aimed to enhance the knowledge and skills of both teachers and students in administering Basic Life Support (BLS) to increase survival chances during emergencies. Method: The activity was conducted at SMP Inspirasi, involving 7 teachers and 42 students. The methods used included interactive lectures, demonstrations, and hands-on practice. It began with a pre-test questionnaire to assess participants’ baseline knowledge of BLS. This was followed by an educational session using presentation slides and group discussions covering BLS concepts and procedures. Trained nurses performed live demonstrations using mannequins. Participants were then divided into small groups for supervised practice. The activity concluded with a post-test and a skills assessment to evaluate improvements in both knowledge and performance. Result: Prior to training, only 2 teachers (28.5%) and 3 students (7.1%) had knowledge of BLS, while 5 teachers (71.5%) and 39 students (92.9%) did not. After the training, all participants (100%) showed significant improvement in both understanding and skill execution. Conclusion: The BLS training was effective in improving school community readiness for emergencies and contributed to the development of community health independence